2016
DOI: 10.1016/j.str.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Impairing Cohesin Smc1/3 Head Engagement Compensates for the Lack of Eco1 Function

Abstract: The cohesin ring, which is composed of the Smc1, Smc3, and Scc1 subunits, topologically embraces two sister chromatids from S phase until anaphase to ensure their precise segregation to the daughter cells. The opening of the ring is required for its loading on the chromosomes and unloading by the action of Wpl1 protein. Both loading and unloading are dependent on ATP hydrolysis by the Smc1 and Smc3 "head" domains, which engage to form two composite ATPase sites. Based on the available structures, we modeled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…This indicates that, regarding ATP hydrolysis at AS1, the main effect of being bound to Rad21-Cter is the reduction of the free-energy barrier. This is in agreement with the experimentally observed fact that the presence of Rad21-Cter allows ATP hydrolysis 27, 35, 36 , lowering the barrier to a calculated ΔG° value close to the range of the experimental free-energy barrier measured for other ATPases, as the F 1 -ATPase (12.9–13.4 kcal mol −1 ) 50 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This indicates that, regarding ATP hydrolysis at AS1, the main effect of being bound to Rad21-Cter is the reduction of the free-energy barrier. This is in agreement with the experimentally observed fact that the presence of Rad21-Cter allows ATP hydrolysis 27, 35, 36 , lowering the barrier to a calculated ΔG° value close to the range of the experimental free-energy barrier measured for other ATPases, as the F 1 -ATPase (12.9–13.4 kcal mol −1 ) 50 .…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that the dimerized head domains of Smc1A and Smc3 hydrolyse ATP in the absence of Rad21 with a nearly undetectable efficiency, but that when they are bound to Rad21-Cter the hydrolysis activity is enhanced 27, 35, 36 . Using our computational approach, we investigate the hydrolysis reaction at the atomic scale, including the identification of the rate-limiting steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the coiled-coil arms may inhibit the Smc ATPase cycle (Figure 3D) to prevent ATPase driven unloading of Smc-ScpAB from chromosomes. ATP hydrolysis mediated unloading has been proposed recently for the related cohesin complex (Elbatsh et al., 2016, Huber et al., 2016). Resolving those exciting alternatives will be crucial for our understanding of SMC complexes, and will possibly require the establishment of single-molecule observations in a purified system.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, it was difficult to envision the mechanistic connection between the heads and the hinges since they are separated by a very long coiled coil and do not bind to each other when expressed as individual domains. Our observation of the collapsed form of cohesin ring suggests that the cycle of ATP binding/ATP hydrolysis, which controls engagement/ disengagement of the heads, 15 is likely to affect the degree to which the arms are coiled around each other. ATP-dependent head engagement promotes dissolution of the Bacillus subtilis Smc rod and is antagonized by the hinge dimerization.…”
Section: The Enigmatic Role Of Atp Hydrolysismentioning
confidence: 88%